2014 Proceedings of the Eleventh Workshop on Analytic Algorithmics and Combinatorics (ANALCO) 2013
DOI: 10.1137/1.9781611973204.9
|View full text |Cite
|
Sign up to set email alerts
|

Small Superpatterns for Dominance Drawing

Abstract: We exploit the connection between dominance drawings of directed acyclic graphs and permutations, in both directions, to provide improved bounds on the size of universal point sets for certain types of dominance drawing and on superpatterns for certain natural classes of permutations. In particular we show that there exist universal point sets for dominance drawings of the Hasse diagrams of width-two partial orders of size O(n 3/2 ), universal point sets for dominance drawings of st-outerplanar graphs of size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…For this reason, the permutations that define planar dominance drawings have no forbidden patterns. However, in later research, we have shown that the dominance drawings of some other classes of graphs have forbidden patterns, leading to smaller universal sets for these drawings [24].…”
Section: Dominance Drawingmentioning
confidence: 82%
“…For this reason, the permutations that define planar dominance drawings have no forbidden patterns. However, in later research, we have shown that the dominance drawings of some other classes of graphs have forbidden patterns, leading to smaller universal sets for these drawings [24].…”
Section: Dominance Drawingmentioning
confidence: 82%
“…A similar but simpler reduction uses S n -superpatterns to construct universal point sets for dominance drawings of transitively reduced st-planar graphs. In subsequent work [4], we study dominance drawings based on superpatterns for 321-avoiding permutations and their subclasses, and we relate these subclasses to natural classes of st-planar graphs and nonplanar Hasse diagrams of width-2 partial orders.…”
Section: Introductionmentioning
confidence: 99%
“…The width of a partial order is the maximum number of elements in an antichain, a set of mutually-incomparable elements. Low-width partial orders arise, for instance, in the edit histories of version control repositories [5]. The treewidth of a partial order is less than twice its width, 1 but partial orders of width w have O(n w ) downsets, tighter than the bound that would be obtained by using treewidth.…”
Section: New Resultsmentioning
confidence: 99%
“…Partially ordered sets of bounded width arise, for instance, in the version histories of a distributed version control repository controlled by a small set of developers (with the assumption that each developer maintains only a single branch of the version history). In this application, there may be many elements of the partially ordered set (versions of the repository) but the width may be bounded by the number of developers [5]. A downset in this application is a set of versions that could possibly describe the simultaneous states of all the developers at some past moment in the history of the repository.…”
Section: Bounded Widthmentioning
confidence: 99%